2019
DOI: 10.29202/nvngu/2019-6/17
|View full text |Cite
|
Sign up to set email alerts
|

Algorithmic provisions for data processing under spatial analysis of risk of accidents at hazardous production facilities

Abstract: Purpose. Rationale of priority areas in the field of hazard analysis at hazardous production facilities (HPF) and the develop ment of a method that allows for spatial analysis of the risk of accidents at a high level of detail. methodology. The authors proposed a method for processing heterogeneous information in order to identify hazardous areas for accidents, based on systematization and processing of source data using expert systems. findings. Using the example of spatial analysis of risk of explosion of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A preventive riskoriented approach [19] can be used as one of the solutions to the problem of collapses and landslide phenomena, which using expert assessment allows analyzing different sections of quarries and dumping sites, and, as a re sult, developing complexes of organizational and technologi cal measures to eliminate the potential danger. The data obtained from the construction of the fault tree showed that a comprehensive solution to the problem is need ed by engaging a riskbased approach and selecting measures to strengthen the ledges of the quarries and dump sites.…”
Section: Fig 2 the Results Of The Analysis Of The Fault Tree For Sitmentioning
confidence: 99%
“…A preventive riskoriented approach [19] can be used as one of the solutions to the problem of collapses and landslide phenomena, which using expert assessment allows analyzing different sections of quarries and dumping sites, and, as a re sult, developing complexes of organizational and technologi cal measures to eliminate the potential danger. The data obtained from the construction of the fault tree showed that a comprehensive solution to the problem is need ed by engaging a riskbased approach and selecting measures to strengthen the ledges of the quarries and dump sites.…”
Section: Fig 2 the Results Of The Analysis Of The Fault Tree For Sitmentioning
confidence: 99%
“…The video recording complex consists of a laptop, from which data of video cameras are recorded, a network cable-twisted pair (12), with which the laptop was connected to a fiber optic path, which consisted of analog-to-digital converters (13) and fiber itself (14). The cameras (16,17) were connected to an analog-to-digital converter using network cables-twisted pairs (15).…”
Section: Resultsmentioning
confidence: 99%
“…Some CCCM, especially those obtained by carbonizing carbon fiber based on organic polymers, are characterized by an increase in strength with an increase in operating temperature up to 2700 ºC. At temperatures above 3000ºC, CCCM are efficient for a short time, since intense graphite sublimation begins (Kabanov et al, 2019;Kolotyrin et al, 2019;Radyuk et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The need to reduce harmful emissions in the air of working areas in open pits complimented by a significant excess of maximum permissible concentrations is described in the works of foreign scientists [31][32][33]. A lot of academic specialists have studied the risk-based approach to the exploitation of hazardous production facilities and have proposed the use of methods of spatial risk analysis [34] and the concept of "Vision Zero" [35]. The dependence of the safety of blasting operations and production efficiency and economic indicators of the products is unconditional [36].…”
Section: Introductionmentioning
confidence: 99%